The Effect of Mediators' Qualities and Strategies on Mediation Outcomes - Dilts, David; Karim, Ahmad (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
This study utilizes discriminant analysis to determine if the characteristics of mediators and the strategies they employ predict the success of mediation in resolving impasses in the public sector in lowa. The data were obtained from questionnaires administered to management and union negotiators in the 214 impasses reported in lowa during 1986. Mediators' characteristics and the strategies they employ are found to predict the success of mediation for both management and union negotiators in lowa during 1986.